Teaching English Through Song To Elementary School Student Of SDN III Ngadiluwih (Experimental Approach) - Nurul, Hidayati (2004)
The objective of this research is to describe the procedure, the result, the advantages and disadvantages of teaching English through song. The material of this research are vocabularies around the school, kinds of music, the uses of "be" for present tense, the uses of "have", the uses of modal "can", and pronoun. The procedures of this study are the teacher plays the song and sing a song together, the teacher gives the story related to the song title and the last the teacher gives treatment related in teaching English. To know the result of teaching English, the writer gives pre-test and posttest. The test is tested to 30 students and each test consists of 30 test items. In pretest, the highest score is 6,6 the lowest score is 2 and the average score is 4,1. In post-test, the highest score is 9 the lowest score is 4 and the average score is 6,2. From the two tests, the writer can analyze that song is more effective. And the conclusion of this experiment is the use of song in teaching learning process can develop the simple English pattern achievement of the sixth years students of SDN III Ngadiluwih. The advantages of teaching English using song are song can motivate, relax and entertain the students. Song also has highly memorable. The disadvantages of teaching English using song are the using of song spending spare time and the classroom will be noisy. Finally, it is suggested to English teachers to apply the song to motivate their students to study better and to improve their achievement.